Economic Exchange During Hyperinflation - Casella, Alessandra; Feinstein, Jonathan S. (Journal of Political Economy, 1990)
Historical evidence indicates that hyperinflations can disrupt individuals' normal trading patterns and impede the orderly functioning of markets. To explore these issues, we construct a theoretical model of hyperinflation that focuses on individuals and their process of economic exchange. In our model buyers must carry cash while shopping, and some transactions take place in a decentralized setting in which buyer and seller negotiate over the terms of trade of an indivisible good. Since buyers face the constant threat of incoming younger (hence richer) customers, their bargaining position is weakened by inflation, allowing sellers to extract a higher real price. However, we show that higher inflation also reduces buyers' search, increasing sellers' wait for customers. As a result, the volume of transactions concluded in the decentralized sector falls. At high enough rates of inflation, all agents suffer a welfare loss.